Opportune Romance: How College Campuses Shape Students' Hookups, Dates, and Relationships. Issue 3 (3rd July 2018) - Allison, Rachel; Ralston, Margaret
ABSTRACT: By merging Online College Social Life Survey data from heterosexual students at 21 U.S. colleges and universities (N = 17, 897) with campus-level data, this article examines the effects of student body size, density, and racial composition on students' hookups, dates, and committed relationships. We examine relationship frequency, whether the most recent of each relationship type occurred with a fellow student, and the effects of racial composition by student race and gender. We find that students at schools with the largest, versus smallest, student body sizes have higher rates of hookups and dates, but are less likely to partner with one another. The percent of white undergraduate students is negatively associated with the number of hookups for white and black women, but positively associated with the number of hookups for Asian women and all Hispanic students, men and women.